Roles and Mechanisms of Dipeptidyl Peptidase 4 Inhibitors in Vascular Aging - Cao, Fen; Wu, Kun; Zhu, Yong-Zhi; Bao, Zhong-Wu (Frontiers in Endocrinology, 2021)
Vascular aging is characterized by alterations in the constitutive properties and biological functions of the blood vessel wall. Endothelial cells (ECs) and vascular smooth muscle cells (VSMCs) are indispensability elements in the inner layer and the medial layer of the blood vessel wall, respectively. Dipeptidyl peptidase-4 (DPP4) inhibitors, as a hypoglycemic agent, play a protective role in reversing vascular aging regardless of their effects in meliorating glycemic control in humans and animal models of type 2 diabetes mellitus (T2DM) through complex cellular mechanisms, including improving EC dysfunction, promoting EC proliferation and migration, alleviating EC senescence, obstructing EC apoptosis, suppressing the proliferation and migration of VSMCs, increasing circulating endothelial progenitor cell (EPC) levels, and preventing the infiltration of mononuclear macrophages. All of these showed that DPP4 inhibitors may exert a positive effect against vascular aging, thereby preventing vascular aging-related diseases. In the current review, we will summarize the cellular mechanism of DPP4 inhibitors regulating vascular aging; moreover, we also intend to compile the roles and the promising therapeutic application of DPP4 inhibitors in vascular aging-related diseases.